الظروف الطارئة وأثرها في عقد الإجارة -جائحة كورونا أنموذجا - زين, ثريا (University of Eloued-جامعة الوادي, 2021)
"يتناول البحثُ جانباً مُهمًّا من جوانب الاجتهاد التنزيلي، وإشكاليتُهُ الرئيسيةُ التي حاول الإجابة عنها تتمحور حول مدى تأثير الظروف الطارئة على عقد الإجارة في الفقه الإسلامي في ظل جائحة كورونا المستجد. وقد جاء الموضوع في ثلاثة مباحث: خصصتُ أولها لبيان معنى الظروف الطارئة وجائحة كورونا، وجعلتُ ثانيها لحقيقة عقد الإجارة وأقوال الفقهاء في فسخها بالأعذار الخاصة، وبيَّنتُ في ثالثها أقوال الفقهاء في أثر جائحة كورونا على عقد الإجارة باعتبارها عذراً عامًّا. وأوصى البحثُ بضرورة حرص الدولة على تحمل المسؤولية لما خلّفتهُ الجائحة من أضرار لجميع الأطراف، وتطبيق العدل والإحسان في كافة المشكلات التي تواجهها. " " The research deals with an important aspect of the descending Ijtihad. Its main problem revolves around the extent to which emergency circumstances affect the lease contract in Islamic jurisprudence in light of the emerging Covid 19 pandemic. The topic came in three sections: I devoted the first to explaining the meaning of emergency conditions and the Covid 19 pandemic. However, the second of it is about the reality of the lease contract and the sayings of the jurists in its annulment with special excuses. Finally, in the third on, I indicated the sayings of the scholars regarding the impact of the Covid 19 pandemic on the lease contract as a general excuse. The research recommended the necessity of the concerned authorities to take responsibility for the damage caused by the pandemic to all parties, and to apply justice and benevolence in all the problems it faces."
مذكرة ماستر
Keywords: جائحة كورونا-الظروف الطارئة, عقد الإيجار; the emerging Covid 19 pandemic- emergency circumstances, lease